Safety and efficacy of dendritic cell vaccine for COVID-19 prevention after 1-Year follow-up: phase I and II clinical trial final result - Jonny, Jonny; Putranto, Terawan Agus; Yana, Martina Lily; Sitepu, Enda Cindylosa; Irfon, Raoulian; Ramadhani, Bunga Pinandhita; Sofro, Muchlis Achsan Udji; Nency, Yetty Movieta; Lestari, Endang Sri; Triwardhani, Ria; Mujahidah,; Sari, Retty Karisma; et al. (Frontiers in Immunology, 2023)
Interim analysis of phase I and phase II clinical trials of personalized vaccines made from autologous monocyte-derived dendritic cells incubated with S-protein of SARS-CoV-2 show that this vaccine is safe and well-tolerated. Our previous report also indicates that this vaccine can induce specific T-cell and B-cell responses against SARS-CoV-2. Herein, we report the final analysis after one year of follow-up regarding its safety and efficacy in subjects of Phase I and Phase II clinical trials. Adult subjects (>18 years old) were given autologous dendritic cells derived from peripheral blood monocytes, which were incubated with S-protein of SARS-CoV-2. The primary outcome is safety in phase I clinical trials. Meanwhile, optimal antigen dosage is determined in phase II clinical trials. COVID-19 and Non-COVID-19 adverse events (AE) were observed for one year. A total of 28 subjects in phase I Clinical trial were randomly assigned to 9 groups based on antigen and GM-CSF dosage. In the phase II Clinical trial, 145 subjects were randomly grouped into three groups based on antigen dosage. 35,71% of subjects in phase I and 16.54% in phase II had Non-COVID AEs during one year follow-up period. No subjects in phase I experienced moderate-severe COVID-19. Meanwhile, 4.31% of subjects in phase II had moderate-severe COVID-19. There is no difference in both COVID and Non-COVID-19 AEs between groups. After one year of follow-up, this vaccine is proven safe and effective for preventing COVID-19. A phase III clinical trial involving more subjects should be conducted to establish its efficacy and see other possible side effects.